2013
DOI: 10.14202/vetworld.2013.1008-1011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative haematology of Vanaraja, Nicobari fowls and their various F1 crosses under hot humid climate of Andaman and Nicobar Islands, India

Abstract: Aim: In the present experiment, the haematological parameters of Vanaraja, Nicobari fowls (Black, Brown and White) and their six F crosses were evaluated. Four erythrocyte traits, six leukocyte traits and one platelet trait were assessed.1 Materials and Methods: Blood samples (1 ml) were collected from the wing vein of each adult bird using 2 ml disposable syringe and then directly transferred to labeled test tube containing anticoagulant EDTA (2 mg EDTA/ml of blood). All haematological parameters were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(1 reference statement)
1
3
4
Order By: Relevance
“…Total TEC and Hb count were significantly (p<0.05) higher in males than females in both seasons. TEC and Hb concentration are lower than the finding in the previous study [ 12 ]. Higher level of TEC count in males is similar to the finding in Vanaraja chickens [ 12 ], colored broiler chickens [ 16 ], and Nigerian local chicken [ 14 ].…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…Total TEC and Hb count were significantly (p<0.05) higher in males than females in both seasons. TEC and Hb concentration are lower than the finding in the previous study [ 12 ]. Higher level of TEC count in males is similar to the finding in Vanaraja chickens [ 12 ], colored broiler chickens [ 16 ], and Nigerian local chicken [ 14 ].…”
Section: Resultscontrasting
confidence: 90%
“…Nosignificant (p>0.05) effect of season was found in TLC and DLC. TLC was lower than the finding in the previous study in Nicobari fowls [12]. Higher level of TLC count in males than females is similar to earlier reports [2,10,14].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Statistical analysis shows significant (P<0.05) difference exists between groups (Table 8 and 9). Kundu et al, (2015) reported FCR of Vanaraja, White Nicobari, Black Nicobari and Brown Nicobari as 2.6, 3.6, 3.9 and 4.17 respectively. 4 th week FCR for Aseel male, Aseel female, Kadaknath male and Kadaknath female were 3.57±0.20, 3.67±0.33, 3.36±0.11 and 2.99±0.15 respectively.…”
Section: Feed Conversion Ratio (Fcr)mentioning
confidence: 97%
“…This chicken is of scavenging type. As per its behavior this chicken is very alert to the social happening such as presence of any intruder in and around their presence by making immediate response to the sound or Kundu et al, 2013). No scientific studies on Sikhar birds had been carried out and no literatures are available on any account of these birds.…”
Section: Introductionmentioning
confidence: 99%